Design of Application for Reporting Violence Against Women and Children in RT.001 RW.005 KEL.Dukuh with Waterfall Method - Abu Sopian; Dedi Setiadi (Jurnal Teknologi Informatika & Komputer)
Violence against women and children is a violation of human rights that occurs across various layers of society, with a significant increase in Indonesia. Data shows that the number of cases of violence against women and children in East Jakarta reached 302 cases in the first six months of 2024. RT.001 RW.005 in the Dukuh Kramat Jati area is one of the areas facing this issue. In this context, incidents of violence are often not addressed or reported swiftly, leading to victims not receiving the protection they deserve. This study aims to design the "Report Violence Against Women and Children" application using the waterfall method, which is expected to make it easier for residents to report cases of violence directly to the RT and RW administrators. Through needs analysis and data collection, this application will provide an efficient solution for report administration. The benefits of this study are not limited to theoretical aspects but also practical ones, with the hope of increasing public awareness and accelerating the handling of violence cases. The outcome of this study is expected to be an application documentation that can be published and copyrighted, thus being accessible to the wider public. This research underscores the importance of information technology in addressing critical social issues, such as violence against women and children, and contributes to the development of a more responsive and effective reporting application.